The Associative Meaning Found in Tourism Advertisements Post on Instagram Social Media: A Semantics Approach - Ananda, Ni Made Likhita; Ni Nyoman Tri Sukarsih; I Gusti Nyoman Putra Kamayana (LPPM Universitas Dhyana Pura, 2025)
This study aimed to identify the types of associative meanings found in the advertisement on Instagram and to analyze the meanings conveyed through the language used in the texts. This study employed a qualitative descriptive approach. The data were collected from selected Instagram captions published on the official @wonderfulindonesia account on November 2024. The results revealed a total of 25 data that reflected different types of associative meanings. Connotative meanings emphasized natural beauty and tranquility, social meanings were related to cultural and traditional values, affective meanings evoked emotional engagement, reflective meanings showed symbolic interpretations, and collocative meanings created thematic unity. These associative elements collectively contributed to a persuasive and meaningful depiction of Indonesia as an attractive tourist destination.